UNCLEAR STATUS OF EMPLOYMENT AGREEMENT IN TERMINATION OF EMPLOYMENT: LEGAL ANALYSIS OF SUPREME COURT DECISION NUMBER 394 K/PDT.SUS-PHI/2023 WHICH DOES NOT GRANT REPLACEMENT MONEY FOR RIGHTS - Syahwa Layli Nabila, Devitria (Indonesian Journal of Labour Law and Industrial Relations, 2024)
Hadiyansyah is an employee from an outsourcing company, namely PT Bina Cipta Abadi, who was assigned to work at PT Yuasa Battery Indonesia with a Specific Time Work Agreement (PKWT). After working for 10 years, Hadiyansyah was terminated by PT Yuasa Battery Indonesia on the grounds of company rationalization as a result of the Covid-19 pandemic, but the company did not provide any compensation to Hadiyansyah. The dispute also occurred because Hadiyansyah considered himself an employee of PT Yuasa Battery Indonesia, but PT Yuasa Battery Indonesia did not admit this. There is also unclear status of the work agreement which Hadiyansyah believes is PKWTT, not PKWT like the initial work agreement. As a legal step, Hadiyansyah filed a lawsuit with PHI. In his considerations, the judge stated that Hadiyansyah's lawsuit had no legal basis and was rejected in its entirety. Hadiyansyah submitted a cassation request to the Supreme Court and part of Hadiyansyah's lawsuit was granted through Supreme Court Decision Number 394 K/Pdt.Sus-PHI/2023. This research aims to determine the legal relationship between Hadiyansyah and PT Yuasa Battery Indonesia, as well as to find out the basis for the judge's consideration of not granting Hadiyansyah's request for compensation for rights. The research method used in this research is normative juridical. The results of this research were that the judge correctly applied the law regarding the legal relationship between Hadiyansyah and PT Yuasa Battery Indonesia which did not exist. As for the compensation money which was not granted by the judge, the author provides an opinion which is the judge's reason, namely the difference in legal interpretation regarding compensation money for leave rights by the Supreme Court, Hadiyansyah's inability to provide evidence, the principles of justice used by the Supreme Court, the Supreme Court Panel of Judges considering legal precedent.